Electromagnetic Interference from Left Ventricular Assist Device (LVAD) Inhibiting the Pacing Function of an Implantable Cardioverter-Defibrillator (ICD) Device. (3rd October 2018) - Erqou, Sebhat; Kormos, Robert L.; Wang, Norman C.; McNamara, Dennis M.; Bazaz, Raveen
Abstract : There is an increasing prevalence of patients with concomitant implantable cardioverter-defibrillators (ICDs) and left ventricular devices (LVADs). The potential for negative interactions between these continually evolving technologies is a valid concern. Previously reported interactions include inappropriate ICD therapy and interference with ICD telemetry function. Understanding the nature of such interactions and developing a comprehensive strategy to approach such situations are important. In this report, we describe a case of electromagnetic interference from LVAD inhibiting the pacing function of an ICD that was corrected by reprograming the device. We would encourage investigators to review patients with ICD and LVAD in their institutions in order to help assess the frequency and nature of these and other interactions.